Goodnight Mister Tom - Magorian, Michelle (Penguin Group, 1983)
Young Willie Beech is evacuated to the country as Britain stands on the brink of the Second World War. A sad, deprived child, he slowly begins to flourish under the care of old Tom Oakley - but his new-found happiness is shattered by a summons from his mother back in London...
Keywords: Juvenile Fiction